Exploring the Relationships Between Mindfulness, Self-Compassion, and Shame. (July 2019) - Sedighimornani, Neda; Rimes, Katharine A.; Verplanken, Bas
Mindfulness has been proposed as an effective tool for regulating negative emotions and emotional disorders. However, little is known about the relationship between mindfulness and shame. The purpose of the current study was to investigate associations between mindfulness, self-compassion, and shame. One-hundred and fifty-nine participants completed the Five-Facet Mindfulness Questionnaire, the Self-Compassion Scale-Short Form, and the Experience of Shame Scale. As expected, both mindfulness and self-compassion were negatively correlated with the experience of shame. In addition, self-compassion was found to fully mediate the relationship between mindfulness and shame. In an effort to explore this relationship further, the associations between specific facets of mindfulness (e.g., observing, describing, acting with awareness, non-reactivity, and non-judgment) and shame were examined. Results showed that the non-judgment facet remains a significant predictor of shame even after controlling for self-compassion. These findings highlight the negative self-evaluative nature of shame, suggesting that shamed individuals may benefit most from interventions that foster non-judgment attitudes toward feelings and thoughts.